Impact of Acute Insulin Resistance on Myocardial Blush in Non-Diabetic Patients Undergoing Primary Percutaneous Coronary Intervention - Kasem, Soheir M.; Saied, Ghada Mohamed; Hegazy, Abdel Nasser MA; Abdelsabour, Mahmoud (Frontiers in Cardiovascular Medicine, 2021)
Background: Myocardial blush grading is considered to be a novel tool for assessment of coronary microvasculature and myocardial perfusion in patients undergoing coronary angiography and angioplasty, and its reduction identifies patients at high risk. Our study aimed to evaluate the association between acute insulin resistance and myocardial blush in non-diabetic patients with ST-segment elevation myocardial infarction (STEMI). Methods: Two hundred forty non-diabetic patients with STEMI who underwent primary percutaneous coronary intervention were consecutively recruited. The relationship of homeostasis model assessment—estimated insulin resistance (HOMA-IR) to myocardial blush and in-hospital outcome was investigated. Results: Higher HOMA-IR tertile was observed in obese patients, with hyperinsulinemia, had Killip class >1, with higher CPK-MB level and was correlated to impaired myocardial blush after adjusting for the other confounding risk factors. It was also concluded that higher HOMA-IR was independently associated with no/minimal myocardial blush after STEMI. Moreover, it was founded to be an independent predictor of pulmonary edema and impaired left ventricular systolic function. Conclusion: This study revealed that acute insulin resistance was prevalent in non-diabetic patients with STEMI and was an independent predictor for post-infarction myocardial and microvascular injury and poor in-hospital outcome. Trial Registration: The trial was registered at the registry of Clinicaltrials.gov, ClinicalTrials.gov Identifier: NCT04651842, Date of registration: 2nd December 2020 Registry URL, https://clinicaltrials.gov/ct2/show/NCT04385589?cond=Dapagliflozin+in+diabetic+patients&cntry=EG&draw=2&rank=1.